2020
DOI: 10.4103/ijpc.ijpc_155_20
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of health care professionals managing non-COVID patients during the COVID-19 pandemic: A descriptive cross-sectional study

Abstract: Context: The coronavirus pandemic has put an unprecedented burden on the health-care workers who are the cornerstone of the work system, preparing to mitigate its effects. Due to the lack of protective equipments, guidelines for managing patients, or proper training and education regarding the same, health care professionals (HCPs) working in non-COVID areas may face even greater problems than those working in COVID areas of a hospital. Our aim was to find out the concerns of HCPs working in non-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians reported the importance of having social support from friends, family, colleagues, and professionals (e.g., counsellors) in 29 studies [ 28 , 30 , 39 , 43 , 44 , 48 , 56 , 58 , 67 , 72 , 78 , 83 , 91 , 99 , 102 , 106 , 115 , 119 , 131 , 150 , 155 , 163 , 172 , 192 , 202 – 205 ]. Several studies ( n = 29) described positive personal coping strategies such as maintaining a positive attitude and resilience [ 37 , 46 , 83 , 100 , 106 , 108 , 136 , 202 , 205 , 206 ], practicing self-care (e.g., physical activity, eating well, resting, engaging in activities they enjoy) [ 30 , 35 , 56 , 65 , 70 , 91 , 102 , 103 , 117 , 119 , 129 , 131 , 150 , 151 , 207 ], and engaging with religious practices [ 39 , 46 , 131 , 205 ] as a way to mitigate negative psychological outcomes. In contrast, two studies reported that physicians engaged in avoidance coping strategies (e.g., screaming, crying, denial, self-blame, disengaging, substance abuse, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Low percentages of anxiety and depression in our study and the previous studies might be attributed to the fact that health care professionals experience high levels of satisfaction from their roles caring for others [ 28 ] and that religious beliefs have supported the positive effects of spirituality on health care professionals [ 29 ]. However, the depressed mood or anxiety exhibited in some healthcare professionals is exacerbated by the extraordinary burden of an augmented work load, inadequate personal protective equipment, the fear of developing COVID-19 virus infection with ensuing infection of friends and relatives, and the need to make ethically tough decisions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shortages of personal protective equipment (PPE) represented significant difficulties ( Slotkin et al, 2020 ). Reduced staff availability hindered routine activities ( Sarma et al, 2020 ). Workers’ mental well-being was under severe strain ( Dubey et al, 2020 , Amin, 2020 , Fernandez et al, 2020 , Lai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rarely used healthcare policies, such as quarantine and patient triage, the implementation of various protective measures, widespread respirator use and new communication technologies were additional stress factors ( Amin, 2020 , Greenberg et al, 2020 ). Moreover, the lack of clear, existing protocols did not allow professionals to work as efficiently and satisfactorily as desired ( Fang et al, 2020 , Sarma et al, 2020 , Slotkin et al, 2020 ). Furthermore, the pandemic may have had a negative impact on the overall quality of care worldwide because of the greater numbers of patients and overloaded, overwhelmed hospitals providing care with fewer resources than usual ( Baker et al, 2020 )…”
Section: Introductionmentioning
confidence: 99%